2012
DOI: 10.1021/ja3043905
|View full text |Cite
|
Sign up to set email alerts
|

Immobilizing Highly Catalytically Active Pt Nanoparticles inside the Pores of Metal–Organic Framework: A Double Solvents Approach

Abstract: Ultrafine Pt nanoparticles were successfully immobilized inside the pores of a metal-organic framework, MIL-101, without aggregation of Pt nanoparticles on the external surfaces of framework by using a "double solvents" method. TEM and electron tomographic measurements clearly demonstrated the uniform three-dimensional distribution of the ultrafine Pt NPs throughout the interior cavities of MIL-101. The resulting Pt@MIL-101 composites represent the first highly active MOF-immobilized metal nanocatalysts for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
562
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 866 publications
(580 citation statements)
references
References 66 publications
13
562
0
5
Order By: Relevance
“…[ 62 ] When used as catalysts, importantly, the obtained NPs/Cu(HBTC)-1 have much shorter diffusion length for substrates than those immobilized within the www.afm-journal.de www.MaterialsViews.com interior cavities of MOFs. [ 63 ] Detailed characterizations of our catalysts are given in Figures S52-S65 (Figure 8 g) indicate that the all the added metals (Au, Pt, and Pd) are uniformly distributed across the nanosheets. In fact, simultaneous mixing of Au precursors with Pt and/or Pd precursors leads to the formation of bimetallic or trimetallic nanoparticles on the Cu(HBTC)-1 supports due to the metal halide anions (AuCl 4 − , PtCl 4 2− , and PdCl 4 2− ) are all negatively charged, together with similar reduction potentials.…”
Section: Anchoring Metal Nanoparticles On the External Surfaces Of Cumentioning
confidence: 99%
“…[ 62 ] When used as catalysts, importantly, the obtained NPs/Cu(HBTC)-1 have much shorter diffusion length for substrates than those immobilized within the www.afm-journal.de www.MaterialsViews.com interior cavities of MOFs. [ 63 ] Detailed characterizations of our catalysts are given in Figures S52-S65 (Figure 8 g) indicate that the all the added metals (Au, Pt, and Pd) are uniformly distributed across the nanosheets. In fact, simultaneous mixing of Au precursors with Pt and/or Pd precursors leads to the formation of bimetallic or trimetallic nanoparticles on the Cu(HBTC)-1 supports due to the metal halide anions (AuCl 4 − , PtCl 4 2− , and PdCl 4 2− ) are all negatively charged, together with similar reduction potentials.…”
Section: Anchoring Metal Nanoparticles On the External Surfaces Of Cumentioning
confidence: 99%
“…Despite of the extraordinary high activity in phenol hydrogenation with hydrogen, Pd/MIL-101 showed much low activity in transfer hydrogenation. This low reactivity is quite unexpected since the Pd/MIL-101 has been shown to be very active in formic decomposition for the production of molecular hydrogen [40]. This result may point to a concerted reaction mechanism for transfer hydrogenation on Pd catalysts.…”
Section: Hydrogen Transfer With Formic Acidmentioning
confidence: 94%
“…[1][2][3][4][5][6] In order to discover novel functional materials in the field of CPs, the rational design and assembly of metal ions and various multifunctional ligands is sensible and effective. [7][8][9][10][11][12] The numerous literatures indicated that utilizing mixed ligands, usually including a multidentate carboxylate ligand and a flexible bipyridyl ligand, to obtain target compound is the most common strategy.…”
Section: Introductionmentioning
confidence: 99%